(untitled) (Літератури світу: поетика, ментальність і духовність, 2017)
The article is devoted to research of the military theme in Ihor Muratov’s poetry in the context of Socialist-realism literature. The poet’s verses, two poems «With Iron and Blood» and «Gate Wide-Open», and also the suite «Loboda the Partisan» were analyzed in detail. The researcher emphasized on the character and peculiarities of the corresponding historical time, which has had the doubtless influence on the formation of the writer’s talent.